2018
DOI: 10.1126/sciimmunol.aan8664
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of human CD4 + cytotoxic T lymphocytes identified by single-cell transcriptome analysis

Abstract: CD4+ cytotoxic T lymphocytes (CD4-CTLs) have been reported to play a protective role in several viral infections. However, little is known in humans about the biology of CD4-CTL generation, their functional properties, and heterogeneity, especially in relation to other well-described CD4+ memory T cell subsets. We performed single-cell RNA sequencing in more than 9000 cells to unravel CD4-CTL heterogeneity, transcriptional profile, and clonality in humans. Single-cell differential gene expression analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
261
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(289 citation statements)
references
References 75 publications
27
261
1
Order By: Relevance
“…Importantly, the absolute CD4 + T cell counts in the clinical blood samples and the numbers estimated from the scRNA-seq analysis showed a strong correlation (R 2 =0.8963, Figure 1F), indicating that the scRNA-seq datasets accurately reflect the cell clusters present in the original blood samples. Figure S2A), which is consistent with a recently described CD4-Tpm cytotoxic cell cluster 35…”
Section: Donorssupporting
confidence: 90%
“…Importantly, the absolute CD4 + T cell counts in the clinical blood samples and the numbers estimated from the scRNA-seq analysis showed a strong correlation (R 2 =0.8963, Figure 1F), indicating that the scRNA-seq datasets accurately reflect the cell clusters present in the original blood samples. Figure S2A), which is consistent with a recently described CD4-Tpm cytotoxic cell cluster 35…”
Section: Donorssupporting
confidence: 90%
“…This is reflected by both the intensity of the cluster's red colour in Figure 2B and the dominant distribution of the red violin in Figure 2C when CMC1 is selected from the DEGs menu. Other DEGs within cluster 3 include CST7, NKG7, KLDR1, GNLY, and GZMH, several of which have been previously associated with cytotoxic T cell function (27). This coincides with the analysis from the original authors of this dataset (26), who identified cells belonging to cluster 3 enriched for CD8+ effector memory CD45RA (CD8 TEMRA ) cells ( Figure 2D) and expression of CCL5 ( Figure 2E), which is a marker of CD8+ TEM cells (26,28).…”
Section: Human Tumour-associated T Cellssupporting
confidence: 84%
“…Very similar clusters of genes were found in single-cell RNAseq analysis of CD4-cytotoxic lymphocytes EMRA cells [33]. The expression pattern of granzymes and killer-like receptors in our clusters suggests that cells in cluster 2 may be the precursors of cells in cluster 1.…”
Section: Scrnaseq Of Ns4b-specific T-cells Reveals Two Distinct Cytotsupporting
confidence: 78%